ADSORPTION BEHAVIOUR OF CARBON DIOXIDE ON MALAYSIAN COAL UNDER DIFFERENT CONDITIONS - ABUNOWARA, MUSTAFA A. (2018)
Sequestration of carbon dioxide (CO2) in coalbed seams is a promising option for mitigating the excessive amount of CO2 emission. However, the amount of CO2 that can be stored in coalbed seam is not well known. Currently, there is a lack of information on CO2 adsorption behaviour of Malaysian coal and its potential for CO2 sequestration.